Low-cost action cameras offer potential for widespread acoustic monitoring of marine ecosystems - Lucille Chapuis (Elsevier, 2021)
Underwater passive acoustic monitoring (PAM) is of growing importance for monitoring the health of aquatic environments. Standard practices use expensive hydrophones to sample soundscapes. They must either be linked to surface recording rigs or use autonomous instrumentation which comes at a premium cost. Although citizen science projects could be of great value to PAM by increasing the number of underwater recordings collected around the world, there is a lack of available low-cost and user-friendly recording hardware. However, consumer-grade action cameras potentially offer an accessible alternative to traditional hydrophones, capable of capturing underwater acoustic recordings.We evaluated the performance of two models of GoPro underwater action cameras deployed as PAM recorders. We tested these cameras against a research-grade hydrophone in a range of shallow tropical sea environments. First, in a sandy area away from reef habitat, we took simultaneous recordings of loudspeaker playbacks of known acoustic signals using all three instruments. We then performed repeated deployments on different coral reef sites in which all three instruments were placed side-by-side to record simultaneously the same natural reef soundscapes. We calculated eight of the most commonly used ecoacoustic indices used in marine soundscape ecology, and assessed the reliability and quantitative accuracy of these compared to the hydrophone.Although not calibrated, GoPros captured recordings from which selected ecoacoustic indices could be calculated reliably, including temporal variability, the acoustic complexity index and acoustic richness. Metrics derived from GoPros can be valuably compared between recordings taken using the same model, but are not directly comparable with hydrophone-derived values. We outline the best settings for collecting soundscape data with GoPros.Underwater action cameras are used frequently by marine scientists, sports enthusiasts and tourists around the world. Their capacity to capture soundscape recordings represents a valuable approach for the global expansion of PAM through citizen science.